Pengaruh Model Pembelajaran Cooperative Learning Tipe Make A Match Terhadap Hasil Belajar Siswa Mata Pelajaran IPAS Kelas IV Di MI Muhammadiyah Tirtosari - Fitri, Salsabilla; Iman, Muis; Nugroho, Irham (Borobudur Islamic Education Review, 2023)
The results of learning science on the material of plant body parts and their functions in class IV MI Muhammadiyah Tirtosari are still relatively low. This is because the teacher uses a direct learning model so that students are not actively involved in learning and tend to be bored. Students will find it difficult to understand the material of plant body parts and their functions. This study aims to determine the cooperative learning model of the make a match type to improve science learning outcomes at MI Muhammadiyah Tirtosari. This study is a quantitative study using an experimental method. The population in this study was 111. From the results of data processing using SPSS version 23, the output results obtained were a df value of 15, a degree of freedom of 0.05 and a t table value of 2.13145. Thus, because the t count value of 14.292> t table 2.13145, as the basis for decision making above, it can be concluded that Ho is rejected and Ha is accepted. So it can be concluded that the application of the make a match type cooperative learning model can improve student learning outcomes on the material of plant body parts and their functions